Performance of Male Athletes in the Brazilian National Handball Team: Youth Category - Santos-Afonso, Max dos; Lourenção, Luciano Garcia; Saes, Mirelle de Oliveira; Ratto, Rafaela da Silva; Afonso, Marla dos Santos; Moraes, Vinícius de (O Mundo da Saúde, 2024)
Injuries and strain in the sports world are caused by the rigidity of training and competitions, combined with the pressure for excellent performance, which can result in musculoskeletal damage. The objective of this study was to analyze the stability and muscle flexibility performance of athletes selected for the Brazilian youth handball team, who participated in the National Development and Technical Improvement Camp. The event included training sessions, video analysis, games, a lecture with a senior national team athlete, and activities such as the official photo and an outing. The athletes were evaluated upon arrival at the camp and after 10 days of immersion in sports activities. A total of 20 athletes, aged 13 and 14, participated, and the effect of pre- and post-training exercises was assessed through the modified sit-and-reach flexibility test and the upper extremity closed kinetic chain stability test. There was a significant improvement in range of motion in most cases, demonstrating a real gain in musculotendinous plasticity and an enhancement in motor performance after the exercise period. Strengthening exercises for the rotator cuff and stretching are crucial to maximizing these gains. Furthermore, the involvement of health professionals, such as physiotherapists and nutritionists, is essential to ensure safe and effective training.